Pemeliharaan Hubungan Antara Ibu Sebagai Orang Tua Asuh Tunggal Dengan Anak - Sessy Refi Sanina; Turnomo Rahardjo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
In general, a whole or a complete family supported by the roles between a father and a mother. Many families end up not living together because of various problems, from divorce to the death of one of the parents. This research is motivated by a singk who experiences problems because of her busy work. It could impact the children with lack of communication and the intensity of face-to-face, which directly affects the quality of the relationship between the mother and her child. This study aims to describe the maintenance of the relationship between Ibu sebagai orang tua asuh tunggals and children using qualitative methods. This study refers to the interpretive paradigm with a phenomenological approach. The subjects of this study were three pairs of informants with mothers who acted as Ibu sebagai orang tua asuh tunggals and had children aged over 17 years, both male and female. The data collected with in-depth interviews technique. The theories used in this study are the theory of Relationship Maintenance, the method of Relational Dialectics, the Role Theory by, and the theory of Equality (Equity Theory). The results of this study indicate that communication patterns between single mother and children have their own way of maintaining relationships, namely in creating positive relationships, closeness, and openness and have different guarantees and assignments. Constraints that often occur between mothers as single foster parents and children occur due to reduced communication intensity, reduced face-to-face frequency and also financial constraints. Effective communication affects the quality of the relationship between mother as a single foster parent and child. The communication patterns applied in this study refer to pluralistic and laissez faire communication patterns. The relationship between a mother as a single mother and a child is not linear, and is always marked by a change, the relationship is always in a changing state when various contradictions arise.